Meanings of health and healthcare in a U.S. border region: a culture-centered approach to health disparities - de Souza, Rebecca; Villegas-Glang, Isabel; Pham, Brianna (Frontiers in Communication, 2025)
Health disparities influence health and health-related outcomes in a multitude of ways, and can be attributed to the unequal distribution of social, political, economic, and environmental resources. This study uses the culture-centered approach (CCA) to illuminate health experiences, meanings, and negotiations of 15 individuals residing in a border region of southern California. Through a qualitative semi-structured interview process, the study identified four main themes: the impact of structural deprivation and stress on health, barriers to U.S. healthcare and transborder negotiations, confronting English hegemony in healthcare interactions, and turning to traditional medicine when biomedicine is unavailable. The study contributes to health disparities research by providing a nuanced exploration of how power dynamics and systemic inequalities shape the experiences of cultural communities as they resist, negotiate, and adapt to inequitable health and healthcare environments. Through amplifying the voices of cultural participants, the study opens alternative pathways for constructing health and puts forth a vision of healthcare rooted in relational and anti-capitalist models of healthcare.